High Resolution Lensless Terahertz Imaging and Ranging - Damyanov, Dilyan; Friederich, Benedikt; Yahyapour, Milad; Vieweg, Nico; Deninger, Anselm; Kolpatzeck, Kevin; Liu, Xuan; Czylwik, Andreas; Schultze, Thorsten; Willms, Ingolf; Balzer, Jan C. (IEEE Access, 2019)
In this paper, we propose a fast terahertz time-domain imaging method using a radar migration algorithm. We demonstrate high-resolution imaging in reflection without any collimating or focusing optics in the terahertz beam. In the proposed method, the sample is illuminated with a divergent terahertz beam, and the receiver collects both specular and diffuse reflections. We further present calibration and post-processing methods that allow us to compensate for the inherently low signal-to-noise ratio of an unfocused terahertz beam. The feasibility of the novel imaging method is demonstrated with geometrically complex samples and a fast terahertz time-domain spectroscopy system based on electronically controlled optical sampling. We show that our concept is capable of generating images of the objects regardless of their size, shape, orientation and position relative to the transmitter and receiver antennas. Objects with edge lengths well below 400 μ m can be clearly detected. The method presented here thus lends itself to arbitrary scenarios and antenna configurations.
CRIS-Team WoS Importer:2019-12-06